Instructional leadership practices in 21st-century education centred schools: a case study of three schools in Gauteng - Mpisane, Sipho (My University, 2020)
This case study explores the Instructional Leadership practices in schools that promote 21stcentury education. To do this, the study investigated what school leaders and educators understand about 21st-century education and its significance today. In addition, the study looks into how instructional leaders inform the curriculum and educator practice in their schools, to prepare learners for the 21st-century. Although there is a wealth of knowledge addressing Instructional Leadership and its value to school improvement, 21st-century education is a growing area in the educational discourse. The two areas of study are yet to converge compelling, leaving a gap in the knowledge base on the role of Instructional Leadership in 21st-century education. Using a qualitative approach, the case study was conducted in three schools in Gauteng. The research participants included Heads of Schools and educators with interviews and questionnaires as the means used for collecting data. The findings indicated a strong leadership presence in the case study schools, with all the Heads of Schools demonstrating sound leadership values. Some Instructional Leadership practices were evident, including a high focus on educator development as an approach for improving educator practice and achieving school goals. The study revealed that although there was some awareness of 21st-century competencies, there was only limited implementation and assessment of 21st-century education in the classroom. The case study schools demonstrated extensive use of technology as a resource for teaching and learning. This study emphasises the need to evaluate Instructional Leadership in the context of 21stcentury educational goals. It makes recommendations for the development of a curriculum that aligns with a framework for the teaching of 21st-century competencies. Lastly, the study highlights the need for educator training to play its part in preparing educators to teach for the 21st-century.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Education by combination of coursework and research to the Wits School of Education, Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2020